Screening for phagocytosis resistance-related genes via a transposon mutant library of Streptococcus suis serotype 2 - Pei, Xiaomeng (Virulence, 2020)
Streptococcus suis serotype 2 (SS2) is a serious zoonotic pathogen which causes symptoms of streptococcal toxic shock syndrome (STSS) and septicemia; these symptoms suggest that SS2 may have evade innate immunity. Phagocytosis is an important innate immunity process where phagocytosed pathogens are killed by lysosome enzymes, reactive oxygen, and nitrogen species, and acidic environments in macrophages following engulfment. A previously constructed mutant SS2 library was screened, revealing 13 mutant strains with decreased phagocytic resistance. Through inverse PCR, the transposon insertion sites were determined. Through bioinformatic analysis, the 13 disrupted genes were identified as Cps2F, 3 genes belonging to ABC transporters, WalR, TehB, rpiA, S-transferase encoding gene, prs, HsdM, GNAT family N-acetyltransferase encoding gene, proB, and upstream region of DnaK. Except for the capsular polysaccharide biosynthesis associated Cps2F, the other genes had not been linked to a role in anti-phagocytosis. The survival ability in macrophages and whole blood of randomly picked mutant strains were significantly impaired compared with wild-type ZY05719. The virulence of the mutant strains was also attenuated in a mouse infection model. In the WalR mutant, the transcription of HP1065 decreased significantly compared with wild-type strain, indicating WalR might regulated HP1065 expression and contribute to the anti-phagocytosis of SS2. In conclusion, we identified 13 genes that influenced the phagocytosis resistant ability of SS2, and many of these genes have not been reported to be associated with resistance to phagocytosis. Our work provides novel insight into resistance to phagocytosis, and furthers our understanding of the pathogenesis mechanism of SS2.